Quark-Antiquark Potential from a Deformed AdS/QCD - Rodrigo C. L. Bruni; Eduardo Folco Capossoli; Henrique Boschi-Filho (Advances in High Energy Physics)
In this work we calculate the static limit of the energy for a quark-antiquark pair from the Nambu-Goto action using a holographic approach with a deformed AdS space, with warp factor exp⁡{(κz)n/n}. From this energy we derive the Cornell potential for the quark-antiquark interaction. We also find a range of values for our parameters which fits exactly the Cornell potential parameters. In particular, setting the zero energy of the Cornell potential at 0.33 fermi, we find that κ=0.56 GeV and n=1.3.